Classroom Management Strategies for Female Teachers Experiencing Empty-NEST - Ellis, Rusnawati; Sampe, Prisca Diantra; Huliselan, Neleke; Makulua, Izak Jakobis (KnE Social Sciences, 2024)
Classroom management is an important, and can impact on an individual's entire life. Classroom management can be influenced by psychological conditions, one of which is empty-nest syndrome. This objective aims to understand classroom management strategies for female teachers who experience an empty-nest. The method in this research is a qualitative, involving two participants who are 50 years old and work as teachers. Data collection used was in-depth interview techniques. The research results show that each individual has their own meaning and experience. Some can apply classroom management strategies positively, but there are also those who interpret them negatively. This will have an impact on all learning conditions, class conditions, and also teacher and student communication. Positive meaning will increase a conducive learning environment, accompanied by positive relationship patterns. This research has implications for the urgency of classroom management and empty-nests for female teachers Keywords: classroom management strategies, empty-nest, female teacher